Tellimya tehuelcha, new species: First record of tellimya brown, 1827, in South America (Bivalvia: Lasaeidae), with notes on life history and reproduction - Zelaya, D.G. (2012)
Fil:Zelaya, D.G. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.